Appropriate Communicative Teams to Improve The Quality of Higher Education from The Perspective of Professors at The University of Batna- Algeria - Nassima Difallah; Iman Benziane (University of Science and Technology, Yemen, 2016)
Abstract: The aim of this study is to determine the appropriate communication teams (Quality circles, brainstorming, benchmarking, and knowledge management) for application in the Algerian higher education institutions in order to improve their quality.We have selected master department at Faculty of Economic Sciences and Management at Batna University who pays great attention to the quality; The study population represents42 professors of Master section without taking the professors experienced less than one year in the department. To achieve objective of the study,a questionnaire was administered in the period from 4-3-2012 until 20 May 2012. Analysis has been effectuated with statistical tools to determine the correlation between two variables (teams and quality).    The study concluded that the professors agree on the appropriate application of communication teams in order to improve the department quality expressed by the ratios: QCs 80%, benchmarking80% , 70% of brainstorming , knowledge management 75% .